Benzodiazepine-induced anterograde amnesia: detrimental side effect to novel study tool - Kaplan, Kameron; Hunsberger, Holly Christian (Frontiers in Pharmacology, 2023)
Benzodiazepines (BZDs) are anxiolytic drugs that act on GABAa receptors and are used to treat anxiety disorders. However, these drugs come with the detrimental side effect of anterograde amnesia, or the inability to form new memories. In this review we discuss, behavioral paradigms, sex differences and hormonal influences affecting BZD-induced amnesia, molecular manipulations, including the knockout of GABAa receptor subunits, and regional studies utilizing lesion and microinjection techniques targeted to the hippocampus and amygdala. Additionally, the relationship between BZD use and cognitive decline related to Alzheimer's disease is addressed, as there is a lack of consensus on whether these drugs are involved in inducing or accelerating pathological cognitive deficits. This review aims to inspire new research directions, as there is a gap in knowledge in understanding the cellular and molecular mechanisms behind BZD-induced amnesia. Understanding these mechanisms will allow for the development of alternative treatments and potentially allow BZDs to be used as a novel tool to study Alzheimer's disease.